JOKOWI’S INITIATIVE FOR A COMPETITION TO CUT INDONESIAN REGULATIONS: RECOMMENDATIONS AND THE ROLE OF HIGHER EDUCATION INSTITUTIONS IN INDONESIA - Abidin, Handa S (Faculty of Law, Universitas Sebelas Maret, 2018)
This research provides recommendations for the development of an initiative of the President of the Republic of Indonesia (Presiden Republik Indonesia), Joko Widodo (Jokowi), namely the implementation of a competition to cut Indonesian regulations, and relates these recommendations to the role of higher education institutions in Indonesia. The concept of “cutting” regulations should be developed into “managing.” The competition should also widen the scope of what should be managed. Rather than being limited only to “regulations,” the scope should include “laws and regulations as well as other relevant law and policy products.” Furthermore, the competition could be a trigger for developing other related collaborations. The collaboration between relevant parties in the competition and other future collaborations can be classified as a form of mutual cooperation (gotong royong) which could contribute to the development of the quality of Indonesian law in general and specifically to the quality of laws and regulations and other relevant law and policy products in the context of Indonesia. This mutual cooperation could also bring direct benefits to the Central Government of the Republic of Indonesia (Pemerintah Pusat Republik Indonesia) and other relevant state-related institutions as well as to higher education institutions in Indonesia that are expected to be involved in the competition and in other future collaborations.